How to identify stroke mimics in patients eligible for intravenous thrombolysis? - Förster, Alex; Griebe, Martin; Wolf, Marc; Szabo, Kristina; Hennerici, Michael G.; Kern, Rolf (Journal of neurology, 2012)
Since decision-making for thrombolysis in acute stroke settings is restricted to a limited time window and based on clinical assessment and CT findings only, thrombolysis is sometimes applied to patients with a final diagnosis other than a stroke. From a prospectively collected stroke/MRI data bank (2004-2010) with 648 suspected ischemic stroke patients treated with rtPA, we identified patients without evidence of acute infarction on follow-up MRI and a final diagnosis other than a stroke or acute cerebrovascular event. We compared demographics, symptoms, complications, and outcome of patients with stroke mimics (SM) to those with acute infarction. In 42 patients, an SM was diagnosed: seizures in 20, conversion disorder in seven, dementia in six, migraine in three, brain tumor in two, and others in four patients. Patients with SM less often had typical stroke symptoms like dysarthria (p < 0.01), facial palsy (p < 0.001), hemiparesis (p < 0.001), horizontal gaze palsy (p < 0.001), and visuospatial neglect (p = 0.03), while aphasia (p = 0.004) and accompanying convulsions (p = 0.01) occurred more often. Independent predictors of SM were known cognitive impairment, aphasia, and accompanying convulsions. Thrombolysis-related complications (orolingual angioedema) occurred in one SM patient and none of the SM patients deteriorated clinically. Stroke mimics comprise neurological/psychiatric disorders and differ from ischemic stroke patients with regard to the clinical presentation at onset. This might be helpful in deciding which patients should undergo acute stroke MRI to rule out SM, facilitate treatment decisions, and reduce the risk of unnecessary therapy.